تحديات تفعيل الأسواق المالية المغاربية وتحقيق الترابط والتكامل فيما بينها - شيخي, غنية; شيخي, خديجة (جامعة الوادي - University of Eloued, 2017)
تتميز أسواق الأوراق المالية المغاربية بجملة من الخصائص تميزها عن غيرها من الأسواق المتقدمة والناشئة، تجعل منها أسواقا متخلفة وضعيفة الأداء، بحيث تواجه أسواق الأوراق المالية في دول المغرب العربي جملة من المعوقات تحول دون انطلاقتها، ويقف وراء هذه المعوقات خصائص البيئة الكلية التي تعمل من خلالها هذه الأسواق سواء منها التشريعية والتنظيمية أو الاقتصادية. كما يقف أمام إمكانية تحقيق أي شكل من أشكال الترابط بين أسواق الأوراق المالية المغاربية مجموعة من العقبات أهمها، هشاشة الترابط بين الاقتصاديات المغاربية، ضعف أو غياب الإرادة السياسية، ضعف القطاع المالي في هذه الدول، قصور الوساطة المالية، عدم توفر الوعي الكافي لدى المستثمر المغاربي وانخفاض رأس المال الشركات المصدرة للأوراق المالية وضعف ملاءتها المالية.بالرغم من الجهود المبذولة من طرف دول المغرب العربي في سبيل تفعيل أسواق أوراقها المالية وتحقيق الترابط والتكامل فيما بينها، إلا أن النتائج المحققة في هذا المجال لازالت ضئيلة جدا وذلك أن هذه الجهود تتطلب إرساء مقومات أساسية تسمح بتوفير المناخ الاستثماري في هذه الدول مع ضرورة اعتماد إصلاحات تمس الجوانب التشريعية والتنظيمية، تطوير المؤشرات الاقتصادية، تنمية المؤسسات المالية في المغرب العربي، نشر الوعي الاستثماري...الخ، كما أن تطوير أسواق الأوراق المالية المغاربية كل على حدى شرط أساسي لنجاح الترابط والتكامل فيما بينها. The challenges of activating the Maghreb financial markets and achieving interdependence and integration among them Maghreb stock markets are characterized by a number of characteristics that distinguish them from other developed and emerging markets, which make them markets backward and underperforming, so that the stock markets in the Maghreb countries face a number of obstacles that prevent them from starting. These obstacles are the characteristics of the overall environment through which they operate. These markets are legislative, regulatory or economic. The weakness of the financial sector in these countries, the lack of financial intermediation, the insufficient awareness of the Maghreb investor, the lack of sufficient political will, the weakness of the financial sector in these countries, Low capital stock issuers and weak financial solvency. Despite the efforts made by the Arab Maghreb countries to activate their securities markets and achieve their interdependence and integration, the results achieved in this area are still very small. These efforts require the establishment of basic elements that allow the investment climate in these countries and the need to adopt reforms The development of economic indicators, the development of financial institutions in the Maghreb, the promotion of investment awareness, etc. The development of the Maghreb stock markets is an essential condition for the success of interdependence and integration among them. The most important efforts and challenges exerted by the Arab Maghreb countries to activate their securities markets are adapting the accounting systems to the international accounting environment, paying attention to corporate governance.
مقال
Keywords: أسواق الأوراق المالية، دول المغرب العربي، الترابط بين أسواق الأوراق المالية المغاربية، الوساطة المالية. stock markets, Maghreb countries, inter-linkages between Maghreb stock markets, financial intermediation.